Case report: Durable complete response of a mucosal melanoma of the rectum after neoadjuvant immunotherapy with ipilimumab plus nivolumab - Krueger, Oskar; Eisenburger, Robin; Tasdogan, Alpaslan; Zimmer, Lisa; Livingstone, Elisabeth; Hadaschik, Eva; Theurer, Sarah; Brodin, Berthold; Schadendorf, Dirk; Ugurel, Selma (Frontiers in Immunology, 2024)
Melanoma causes the majority of skin cancer-related deaths. Despite novel therapy options, metastatic melanoma still has a poor prognosis. Immune checkpoint inhibition (ICI) therapy has been shown to prolong overall survival in patients with advanced melanoma, but mucosal melanomas respond less favorably compared to melanomas of cutaneous origin. We report on a patient with a mucosal melanoma of the rectum diagnosed in June 2020. Since a surgical intervention in order to achieve a tumor-free situation would have required an amputation of the rectum, a neo-adjuvant systemic immunotherapy with ipilimumab and nivolumab was initiated. As restaging and colonoscopy after four doses of this combination immunotherapy showed a partial response, the patient decided against the pre-planned surgery and a maintenance therapy with nivolumab was started. Repeated colonoscopy showed a complete response after four doses of nivolumab. After ongoing ICI therapy with nivolumab and no evidence of tumor relapse, immunotherapy was stopped in July 2022 after nearly 2 years of continuous treatment. The patient remained tumor-free during further follow-up. Neo-adjuvant immunotherapy is getting more explored in advanced melanoma. By administering ICI therapy before surgical resection of an essentially operable tumor, a stronger and more diverse immunological response is supposed to be achieved. Our reported case demonstrates that this approach could also be effective in mucosal melanoma despite of its generally lower response to immunotherapy.